Comorbidity Prevalence and Impact on Quality of Life in Gay and Bisexual Men Following Prostate Cancer Treatment. Issue 6 (8th October 2021) - Haggart, Ryan; Polter, Elizabeth; Ross, Michael; Kohli, Nidhi; Konety, Badrinath R.; Mitteldorf, Darryl; West, William; Rosser, B.R.Simon
Abstract: Introduction: Studies have demonstrated worse health related quality of life (HRQOL) outcomes in gay and bisexual men (GBM) following prostate cancer treatment compared to heterosexual men potentially due to differences in comorbidity burden. Aim: To establish the prevalence of comorbidities and their association with HRQOL metrics in GBM following prostate cancer treatment. Methods: We evaluated HRQOL and prevalence of comorbidities in 193 GBM from the United States and Canada in a cross-sectional, online survey: the Masked for Review. HRQOL was measured with the Expanded Prostate Cancer Index Composite (EPIC) and the 12-Item Short Form Health Survey (SF-12). Main Outcome Measures: Our outcomes included comorbidity prevalence, mean differences for HRQOL scores by comorbidity status, and mean differences for HRQOL by comorbidity count. Results: GBM were found to have a higher prevalence of blood vessel disease and mental health disorders but lower prevalence of obesity and type 2 diabetes when compared to published data in general prostate cancer populations. Statistically significant reductions in HRQOL metrics were associated with mental health diagnoses, diabetes, and obesity. Increased number of comorbidities was also associated with reductions in HRQOL metrics in nearly all categories. Conclusion: These results suggest that the worse QOL outcomes in GBM following prostate cancer treatment may be due to differences in comorbidity burden. This study is the first to evaluate the relationship between comorbidities and HRQOL outcomes in GBM. Limitations of this study include a small sample size and cross-sectional study design. If confirmed in larger, longitudinal, clinically confirmed studies, these findings indicate a need to intervene on and consider comorbidities in GBM diagnosed with prostate cancer.